An evaluation of the impacts of transaction cost and market outlet risks on market partcipation of smallholder dairy farmers in Central Kenya. - Ngigi, M.W. (University of Nairobi, 2002)
The objective of this study is to characterise the marketing system in which smallholder dairy farmers (SDF) in Kenya operate and to examine how transaction costs (TCs) and market outlet risks (MORs) influence market participation of the farmers. The study begins with a critical review of the evolution of the country's dairy marketing policies, right from the introduction of commercial dairying in the country at the beginning of the 20th century to the period of the study. Economic actors, including organisations, receive special attention as the prime instigators of institutional changes. The importance of history in conditioning future institutional structures makes such a review a fundamental element in placing the prevailing marketing system in proper perspective. The review shows that Kenya's dairy industry has been a very dynamic industry that has evolved as circumstances are altered. Specifically, the review identifies three major policy turning points, triggered by a great variety of causes all of which generated conditions that both facilitated and constrained SDF production and market activities. The review also illustrates that the behavior of organizations and their relationships with the central administration can set the conditions for an entire industry's development. It also provides a useful starting point for the core objective of the 'study, which is based on the analysis of primary farm- and market- level longitudinal and cross-sectional data using appropriate statistical and econometric methods. High perishability and the daily pattern of flow of milk output (at least within a lactation period), which necessitate repetitive tasks of milk sales activities, are the principal sources of TCs and MORs associated with sale of milk. However, while the TCs and MORs inherently arising from these aspects of milk production and marketing potentially face all dairy farmers, the characteristics pose greater challenges to the SDF. This is due primarily to quantity constraints associated with small marketable surpluses and because of market accessibility problems characterising most rural areas. Analysis of the primary data reveals that an average SDP in the study area marketed about 9 litres of milk per day and was located about 4.3 kilometres away from a major road. Together, quantity constraint and market accessibility are found to have significant influence on SDF's market participation with respect to choice of market outlet. The study reveals that the SDP in the study area operated in a marketing system where: (i) feasible market outlet alternatives varied widely with accessibility to major roads and consumption centers; (ii) size of household's marketable surplus played a significant role in influencing both the choice of market outlet and SDP decisions on whether to sell to cash-sale or to credit markets, and what proportion of milk to allocate to each; and (iii) unit milk prices differed widely with market outlet and contractual arrangements with respect to time pattern of payment. A price decomposition model based on the ordinary least squares (OLS) method is used to make comparison of values across the observed modes of payment. The results present strong evidence that transactions involving regular payments by fixed schedules offered lower unit prices relative to spot-cash transactions. In the context of the study, the price differentials are interpreted as revealing compensating differentials across the contractual arrangements with regards to market search, market assurance and savings utility. Spot-cash markets for the highly perishable commodity expose the SDF to greater risks of non-sale. On the other hand, contractual arrangements involving payments at regular fixed schedules implicitly define repeat contracts that 'routinize' milk sales/delivery tasks, offer greater assurance to the farmer for subsequent sales, as well as creating savings utility. Relative to spot-cash prices, the respective price differentials indicate the amount (in cash per litre of milk) the SDF were, on the overall, willing to sacrifice for the benefits of the corresponding flows of payments. The model results suggest that fortnightly payments attracted by far the largest sacrifice of 18%, next highest sacrifice (J 0%) was for cash-repeat payments followed by monthly (7%) and least was weekly payments (5%). Further analysis suggests that household-specific socio-economic factors had significant conditioning effects on preferences for the modes of payment. Results from applications of random-effects logit and Tobit models show that, ceteris paribus, younger, more educated producers were more likely to accept sales on credit. Conversely, older producers with more experience but less formal education were more likely to sell for cash rather than credit. The results also suggest that the desired liquidity flow was an important criterion for market choice behaviour. Where liquidity flow was required in lumps to match lumpy expenditures, on-credit sales were preferred. A basic conclusion of the study is that smallholder's market-outlet choice behaviour is not based on the levels of price alone; it is also influenced by some other important contractual elements of exchange. The study recommends that comparisons of producer's market-outlet choice behaviour should be based on sound and objective theoretical and empirical analysis of differentials in benefits derived by the producer from the different contractual arrangements offered by the existing marketing system. In particular to milk marketing, this study shows that a particularly important contractual element relates to the time pattern of payments. The findings of the study have important implications for the basic structure of the first point of sale of milk under liberalized market conditions. Differentiated producer-preferences for modes of payments, coupled with buyers' need to mini mise TCs involved in procuring milk from SDF, imply that the first point of sale of milk will continue to be characterised by a wide range of marketoutlets, each tailoring its major marketing strategy towards one of SDFs' preferred modes of payment. This further implies that mode of payment is a potentially powerful competitive tool as opposed to offering generalised sales arrangements for all sellers. Participation of Dairy Farmers' Co-operative Societies (DFCS) seems to be on the decline. Collective marketing by SDFs nonetheless remains potentially useful in reducing TCs and MORs. This is clearly demonstrated by a spontaneous emergence of new organisational forms of collective milk marketing based on smaller-sized groups of self-selected farmers as opposed to the large-sized DFCS based on open membership. Such institutional innovation clearly implies that exogenously prescribed organisational structures may not be as effective and responsive as farmer-evolved processes, such as learning and incremental innovations. Therefore, government policy must promote an environment that induces smallholder farmers to make incremental innovations in organisational types and governance structures appropriate for the diverse market outlet types and modes of payment.